Pemberdayaan Madrasah; Upaya Meningkatkan Kualitas Pendidikan Islam - ali murtadho (Jurnal Penelitian Pendidikan, 2012)
Abstract:In the history of Moslem education, the history of Islamic Schools development will always beatractive to be analized critically. The study is being urgent because it is expected that theIslamic schools will have some roles in the Moslem education development objectively andcomprehensively. It is regarded as the important one because in every phase of Islamic schools’development is always found some efforts to be better, the innovation, and other improvements.Islamic school is one of the Islamic isntitutions of education in Indonesia. The islamic schoolhas long cronology on its development. Since it is formed until now, there are someimprovements which are trasforming the Islamic education institutions to be qualified which aresupported by the Moslem reformers. The lack of the awareness of the Moslem educationimportance in Indonesia in the beginning of Islamic schools’ development is felt by the Moslemdoers of education. That is why, the Islamic schools should be forceful.